1976
DOI: 10.1111/j.1744-7348.1976.tb01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical suppression of the symptoms of two virus diseases

Abstract: Carbendazim applied at the rate of z g per plant to the roots of tobacco (Nicotiana tabacum cv. White Burley) plants before infection with tobacco mosaic virus (TMV) caused very considerable reduction in the severity of disease symptoms in systemically infected leaves but did not affect their virus content. Leaves of untreated, infected plants had a greatly reduced chlorophyll content IOO days after infection whereas the chlorophyll content of leaves of infected plants treated with carbendazim was similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Tomlinson et al (1976) demonstrated that fungicides such as Benlate and Bavistin, which contain methyl benzimidazole-2-yl-carbamate (MBC or carbendazim), reduced the severity of mosaic symptoms caused by TMV in tobacco, and yellowing symptoms produced by beet western yellows virus in lettuce. Recently, however, some systemic fungicides have been shown to suppress virus symptoms when applied to diseased plants, without necessarily reducing the concentration of virus within the plant.…”
Section: Control Of Disease Symptoms By Chemicalsmentioning
confidence: 99%
“…Tomlinson et al (1976) demonstrated that fungicides such as Benlate and Bavistin, which contain methyl benzimidazole-2-yl-carbamate (MBC or carbendazim), reduced the severity of mosaic symptoms caused by TMV in tobacco, and yellowing symptoms produced by beet western yellows virus in lettuce. Recently, however, some systemic fungicides have been shown to suppress virus symptoms when applied to diseased plants, without necessarily reducing the concentration of virus within the plant.…”
Section: Control Of Disease Symptoms By Chemicalsmentioning
confidence: 99%
“…Part of the effect was attributed to a reduced ability of the aphid vectors to colonise treated plants, but an effect on susceptibility of treated plants to virus was also possible . Methyl benzimidazol-2yl carbamate (MBC), the water decomposition product and fungitoxic principle of the benomyl fungicides (28), inhibited formation of visible symptoms of TMV on tobacco and beet western yellows virus (BWYV) in lettuce (143) . Other studies showed that the multiplication of TMV in tobacco was strongly inhibited (46), and that MBC treatment completely prevented the normal inhibition of plant growth resulting from TMV infection (47) .…”
Section: Chemotherapymentioning
confidence: 99%
“…In many cases juvenile tissues such as meristems are known to support little or no virus multiplication (29,129,131) . MBC was found to be ineffective against several other viruses (11, 143) .…”
Section: Chemotherapymentioning
confidence: 99%
“…This leaf-age-dependent effect may be a possible explanation for the discrepancies found in the literature in relation to the effects of kinetin and benzimidazole derivatives on systemic hosts (BAILISS, COCKER and CASSELS 1977, FRASER and WHENHAM 1978, TOMLINSON, FAITHFULL and WARD 1976. In earlier investigations we demonstrated the existence of a "cytokinin gradient" in tobacco plants (BALAZS, BARNA and KIRALY 1976b) and showed that exogenously applied cytokinins had different effects on leaves of different Ages.…”
Section: Results and Conclusionmentioning
confidence: 72%
“…1976a, BALAZS, BARNA and KIRALY 1976b, SZIRMAI 1964, KIRALY, EL HAMMADY andPOZSAR 1968), there are conflicting reports as regards the effects on symptoms and virus multiplication in the case of a systemic host (BAILISS, COCKER and CASSELS 1977, FRASER and WHENHAM 1978, TOMLINSON, FAITHFULL and WARD 1976. These contradictory results may due to the different hosts and viruses used in those experiments as well as to treatments carried out in different ways, including the time of treatment (whether before or after inoculation with the virus) (ALDWINCKLE 1975).…”
mentioning
confidence: 99%